Role of fibroscan in assessing the extent of liver involvement among chronic hepatitis B and C cases - Jyothi, Pendyala; Vanisree, Dasari; Murty, Durbha Satyanarayana; Prasanthi, Kolli (ScienceRise: Medical Science, 2022)
Chronic liver diseases (CLD) cause significant morbidity and mortality worldwide, accounting for approximately 2 million deaths annually. The majority of CLDs include alcoholic liver disease, chronic viral hepatitis, including hepatitis B and C, non-alcoholic fatty liver disease (NAFLD), and hemochromatosis. Of these, hepatitis B virus (HBV) and hepatitis C virus (HCV) infections account for a substantial proportion of liver diseases which is responsible for liver damage ranging from minor disorders to liver cirrhosis and hepatocellular carcinoma (HCC). Fibroscan is a novel non-invasive method for assessing hepatic fibrosis by measuring liver stiffness. The aim. The present study was conducted to know the prevalence of blood-born viral pathogens (HBV, HCV) among patients with chronic liver diseases (CLD) and also to assess the role of Fibroscan and liver function tests (LFT) in evaluating the extent of chronic liver disease. Material and methods: The present study comprised 100 chronic liver disease patients attending the gastroenterology department. All the chronic liver disease cases were tested for Hepatitis B and Hepatitis C viral infections using a rapid Immunochromatography assay. Simultaneously they were subjected to liver function tests and fibroscan to assess the extent of fibrosis by staging from F0 to F4. Results: When screened for bloodborne viral pathogens, 46 % were HBV positive, 10 % were HCV, and none were HIV positive. No co-infection was detected. HBV was identified as the most typical cause of CLD in about 46 %, followed by non-viral/non-infectious (alcoholic, metabolic, autoimmune) cause in 44 % and 10 %, the cause for CLD was HCV. As per fibroscan results, 80 % of HCV and 39 % of HBV patients were in the stage of cirrhosis/advanced fibrosis. Conclusion: HBV was the predominant cause of CLD. Liver stiffness has recently been shown to be a good predictor of clinical outcomes. A fibroscan will help in the decision-making process in staging the disease and choice of treatment in viral hepatitis cases